Monumental Constructions of Bilyar: a new look. “Juma Mosque” - Zilivinskaya Emma D. (Поволжская археология, 2019)
The paper considers the monumental structures of Bilyar located in the citadel of the fortified settlement. The Juma Mosque of Bilyar and other social buildings were studied in the 1970s. Their reconstructions made in the same period of time become canonical. The consideration of Bilyar buildings in the context of the architecture of the entire Muslim world allows to make certain adjustments both in the interpretation of the buildings and in the elements of their reconstruction. An analysis of the remains of the mosques suggests that an initially constructed wooden mosque was later dismantled and replaced with a stone building. Both mosques were rectangular in plan, and their interior was subdivided into aisles by rows of columns. The author concludes that this type of layout is characteristic of Asia Minor mosques of the Seljuk period.